Phase-feeding strategies based on lysine specifications for grow-finish pigs(1) - Menegat, Mariana B (J Anim Sci, 2019)
Four experiments were conducted using 1,100 to 1,188 pigs each (PIC 359 × 1,050) from ~27 to 127 kg BW to evaluate phase-feeding strategies based on Lys specifications and number of dietary phases for grow-finish pigs. Different phase-feeding strategies were used in each experiment with treatments consisting of a combination of 3 Lys specifications at 96%, 98%, or 100% of estimated requirement for growth rate and 4 phase-feeding strategies with 1, 2, 3, or 4 dietary phases. A single-phase-feeding strategy reduced (P < 0.05) overall growth performance, live BW, and HCW whether Lys specifications were at 98% or 100% of estimated requirements compared with multi-phase-feeding strategies. Lysine specifications at 96% of estimated requirements in a 4-phase-feeding strategy reduced (P < 0.05) overall growth performance compared with feeding strategies with Lys at 100% of estimated requirements, unless Lys specifications were increased to 100% of estimated requirements in the late finishing phase. Lysine specifications at 98% or 100% of estimated requirements in a 2-, 3- or 4-phase feeding strategy led to similar (P < 0.05) overall growth rate, live BW, and HCW of grow-finish pigs. Pigs fed 1, 2, or 3-phase feeding strategies or feeding strategies with Lys below the requirements in early grow finish had improved growth performance driven by improved feed efficiency in the period following low Lys levels, indicating the occurrence of compensatory growth. For carcass characteristics, there was no evidence (P > 0.10) for differences in carcass yield, back fat, loin depth, or lean percentage across feeding strategies in any of the experiments. In conclusion, phase-feeding strategies provide performance advantages over feeding a single dietary phase throughout the grow-finish period. Simplification of feeding strategies from 4 to 3 or 2 dietary phases with Lys specifications at 98% to 100% of estimated requirements for growth rate does not compromise overall growth performance and carcass characteristics of grow-finish pigs from 27 to 127 kg BW. Although, using feeding programs with fewer dietary phases and Lys set slightly below the requirements can compromise growth performance if initial BW and feed intake in the grow-finish period are lower than expected.